Management of Surface and Underground Water: A Possibility to Improve Irrigation Effectiveness (International Journal of Innovative Research in Computer Science & Technology, 2022)
Conjunctive usage management may be used  in a variety of contexts, and there do not seem to be any  instances where it should not be used. Conjunctive usage  management that is planned is much superior to spontaneous  conjunctive use. The majority of the development has already  happened, and there are unlikely to be any new “Greenfield”  irrigation projects on a large scale. Most conjunctive usage  administration shall be implemented by retro-fitting  supervision structures to prevailing schemes. In irrigation  regions, poverty reduction is strongly related to effective  supply of water and, as a result, to conjunctive usage  administration. The most significant setting for management  methods will be the regulatory framework for water  management for various sovereign states. Any institutional  improvement will need significant policy and perhaps  legislative reforms to be effective. Conjunctive usage  administration shall be connected to autonomous strategies on energy, climate change adaptation, and food security,  necessitating a more comprehensive government strategy.  Documentation of the actual overall rate of water assets and  the distinct charge to different people is an essential  component of planned conjunctive usage (for example,  electricity subsidies are very common). The overall actual  cost and the cost of each individual water consumer may be  very different. The degree of surface and groundwater  connection is an essential technical issue, but it will have  little impact on whether conjunctive use management is  effective. In most cases, established solidification surrounding groundwater management and the establishment  of a fully integrated water agency would be a significant  issue. Conjunctive usage management will include a  significant amount of public education and technical  evaluations.
Keywords: Conjunctive Usage; Environmental Advantage; Irrigation Effectiveness; Irrigation Efficiency; Water Management